Analisis Faktor-Faktor Yang Mempengaruhi Underpricing Saat Initial Public Offering Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2014 - Hanivah, Dyah Ayuk Siti; , Dra. Rina Trisnawati,Ak,M.Si,Ph.D (2016)
Underpricing is a phenomenon which the current share price the Initial Public Offering lower than the price of shares traded on the secondary market. Companies that do Initial Public Offering avoid underpricing, because companies do not get maximum funds from the sale of shares premiere. This study aims to examine the factors - factors that affect the level of Underpricing period 2010-2014. The population used in this study are all companies that conduct an Initial Public Offering on the Indonesia Stock Exchange (BEI) in 2010 - 2014. The research sample was determined by purposive sampling method. The samples used were 72 companies. Hypothesis testing using multiple regression analysis. The model results of this study show that (1) Reputation Underwriter has no effect on underpricing; (2) Age Company has no effect on underpricing; (3) The Company size has no effect on underpricing; (4) Financial Leverage (FL) has no effect on underpricing; (5) The auditor's reputation has a significant effect on underpricing; and (6) Return on Assets (ROA) has a significant effect on underpricing. This means that the level variables and ROA Auditor Reputation can affect the level of underpricing.